Tekanan kerja dalam kalangan guru : Kajian di sebuah sekolah menengah Daerah Kluang Johor Darul Takzim - Noraini, Mohamad (2015)
Job stress is normal in our lifes today that could either positive or negative impression to the individual. Among the factors that contributed to the stress is the over workload, time constraints, bad relationship between teachers and students and principal support. Therefore it is crucial to know whether these same factors existing in contributing to job stress in the workplace in Malaysia. Thus, this study aims to identify factors that contribute to work stress among teachers in Malaysia. The population of this study are the teachers at a secondary school in Kluang, Johor. A total number of 148 questionnaires were distributed to the respondents. However only 116 can be used for data analysis. The level of job stress are at a moderate level. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 22 for correlation analysis and multiple regression. The study also identified the relationship between the independent variables and the dependent variable. Overall, this study has shown that time constraints and unhealthy relationships among teachers and students have a positive relationship and a significant impact on job stress among teachers. However the over workload and support from principal do not have a significant on the job stress among teachers